Diatom diversity in a mountain lake in southern European Alps (Italy) - Ciutti, Francesca; Blanco, Saúl; Bertoli, Marco; Pizzul, Elisabetta; Pastorino, Paolo; Prearo, Marino; Cappelletti, Cristina (Phytotaxa, 2025)
Mountain lakes, often regarded as sentinels of environmental degradation and climate change, are extreme environments. Diatoms are widely considered good indicators in freshwater ecosystems. Littoral diatoms in lakes are highly effective in detecting trophic and thermal conditions and point-source pollution and are considered early warning of potential changes in lake ecosystems. An extensive study of littoral diatoms of Upper Lake Balma (southern European Alps, Italy) was conducted in 2021. Sampling was carried out at seven littoral stations over two periods (July and October). The results revealed a high diversity of taxa, with a total of 116 identified. Plates with figures for 103 taxa and measures (length, width and striae/fibulae number) for 104 taxa are given. Iconographic studies significantly enhance the description of diatom biodiversity in these environments.